ANALISIS HUBUNGAN KADAR KIDNEY INJURY MOLECULE -1 (KIM-1) DENGAN LAJU FILTRASI GLOMERULUS PADA PASIEN DIABETES MELITUS TIPE 2 - Mutiah Dwi Humairah; Uleng Bahrun; Liong Boy Kurniawan (Poltekkes Kemenkes Pakassar, 2021)
Diabetes melitus type 2 (DM Type 2) is a disorder characterized by an increase in blood glucose and has become a world health problem due to high rates of morbidity and mortality. Complications of DM occur because glucose levels in the blood are not well controlled, one of which is diabetic nephropathy due to glomerular damage. Renal function monitoring is usually increased in patients with kidney damage, so KIM-1 plays a role in the development of interstitial fibrosis in kidney disease and can be used to indicate early kidney damage as in several studies that have shown the role of KIM-1 as a tubular biomarker in cases of DM. This study aims to analyze the relationship between levels of Kidney Injury Molecule – 1 (KIM-1) with Glomerular Filtration Rate (GFR) in patients with type 2 Diabetes melitus. The data in this study used 60 subjects consisting of 43.33% male and 56.67 % are female. KIM-1 levels were checked using the ELISA method. The results of this study showed that the mean GFR was 103.82 ml/min/1.73m2 and the average KIM-1 level was 1.887 ng/mL. Statistically, it shows that there is a strong correlation in a negative direction between the GFR and KIM-1 variables (r=-0.657 p=<0.001), the higher the GFR value, the lower the KIM-1 value, and vice versa. The conclusion shows that there is a relationship between Kidney Injury Molecule-1 levels and Glomerulus Filtration Rate in type 2 Diabetes melitus patients